Strategi Digital Marketing: Dampak Influencer, Iklan Berbayar, dan Desain Visual terhadap Perilaku Pembelian Konsumen: Digital Marketing Strategies: The Impact of Influencers, Paid Ads, and Visual Design on Consumer Purchasing Behavior - Nuryani, Hanifa Sri (Al Dzahab, 2025)
Purpose: This study aims to empirically examine the effects of influencer marketing, paid advertising, and visual design on consumer purchasing decisions within the context of digital marketing in Sumbawa Regency. Design/Methodology/Approach: A quantitative approach with an explanatory research design was employed to explain the causal relationships among variables. The sample consisted of 150 consumers in Sumbawa Regency, selected using purposive sampling. Data were collected through an online questionnaire and analyzed using the Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS) with SmartPLS 4 software. Findings: The results indicate that influencer marketing, paid advertising, and visual design each have a positive and significant effect on consumer purchasing decisions. Collectively, these three independent variables explain 74.3% of the variability in purchasing decisions, demonstrating strong predictive power of the model. Research Implications: Effective digital marketing strategies must be integrated. To enhance consumer purchasing decisions, companies cannot rely on a single tactic but should instead combine the authentic persuasive power of influencers, the precise reach of paid advertising, and the credibility appeal of visual design synergistically to create a holistic and competitive marketing ecosystem.